2013
DOI: 10.14233/ajchem.2013.13943
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative and Anti-inflammatory Effects of Flavonoids from the Silk of Zea mays Linn

Abstract: Reactive oxygen species such as superoxide anion, hydroxyl radical and peroxynitrite have been reported to play a critical role in the process of inflammation in various tissues. In skin, reactive oxygen species can be produced by chemical ionization, UV radiation and enzymatically by polymorphonuclear leukocytes that infiltrate the sites of infection 1 . Excessive reactive oxygen species cause extensive damage to DNA, proteins and lipids and have been reported to be pro-inflammatory mediators 2 .Inducible nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The aqueous extract (200 mg/kg) showed a notable decrease in the edema volume at 1 h and 3 h, whereas the ethanol extract exhibited a potent reduction in the edema volume only at 2 h, but the mechanism involved has not been elucidated. Similarly, chrysoeriol isolated from the silk of Z. mays could play crucial roles as an anti-inflammatory agent that has strong in vitro actions on the expressions of COX-2 proteins and iNOS in LPS-induced HaCaT human keratinocyte cells as revealed by using Western blotting [18]. Moreover, in their in vivo and in vitro experimental models, Csupor et al [73] demonstrated that chrysoeriol obtained from the chloroform extracts of Centaurea sadleriana exhibited significant effects on COX-1 and COX-2 enzymes.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aqueous extract (200 mg/kg) showed a notable decrease in the edema volume at 1 h and 3 h, whereas the ethanol extract exhibited a potent reduction in the edema volume only at 2 h, but the mechanism involved has not been elucidated. Similarly, chrysoeriol isolated from the silk of Z. mays could play crucial roles as an anti-inflammatory agent that has strong in vitro actions on the expressions of COX-2 proteins and iNOS in LPS-induced HaCaT human keratinocyte cells as revealed by using Western blotting [18]. Moreover, in their in vivo and in vitro experimental models, Csupor et al [73] demonstrated that chrysoeriol obtained from the chloroform extracts of Centaurea sadleriana exhibited significant effects on COX-1 and COX-2 enzymes.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…In addition, the anticancer effect of chrysoeriol has been reported in vivo [11,13] and through in silico molecular docking against several cancer receptors [14]. On the other hand, chrysoeriol has showed an anti-inflammatory effect in several in vitro studies [15][16][17][18][19][20]. In animal models, it has ameliorated acute skin inflammation [21] and exhibited reno-protection against acute kidney injury [22].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that luteolin had strong DPPH (IC 50 = 13.85 � 0.23 M), superoxide anion scavenging activity (IC 50 = 1.64 � 0.07 M), and dose-dependent inhibition induced the expression of nitric oxide synthase protein and the mRNA level of cyclooxygenase-2. [122] A rat model of carrageenin-induced pleurisy studied the anti-inflammatory activity of CS aqueous extract (CSEX). Pretreatment with CSEX could reduce exudate, leukocyte count, oxidative stress, C3 protein level, and O 2 À level in inflammatory sites.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Western blot and real‐time polymerase chain reactions were used to quantify the protein and mRNA levels of inducible nitric oxide synthase and cyclooxygenase‐2 in lipopolysaccharide‐stimulated HaCaT cells to determine the anti‐inflammatory activity of chrysoeriol‐6‐ C‐β ‐boivinopyranosyl‐7‐ O‐β ‐glucopyranoside, chrysoeriol, and luteolin. The results showed that luteolin had strong DPPH (IC 50 =13.85±0.23 M), superoxide anion scavenging activity (IC 50 =1.64±0.07 M), and dose‐dependent inhibition induced the expression of nitric oxide synthase protein and the mRNA level of cyclooxygenase‐2 [122] …”
Section: Pharmacological Activitiesmentioning
confidence: 99%